PYROLYSIS OF BAGGASE WITH Ni/SBA-15 CATALYST USING PYROLYSIS GAS CHROMATOGRAPHY MASS-SPECTROMETER (Py-GC/MS) - Praskianto, Ahmed Iqbal; Subagyono, R. R Dirgarini J.N.; Allo, Veliyana Londong (PROSIDING SEMINAR KIMIA, 2023)
Pyrolysis experiments of bagasse with catalyst Ni/SBA-15 at 350°C, 450°C and 550°C using a Pyrolysis-Gas Chromatography-Mass Spectrometer (Py-GC/MS) been done. This study aims to determine the chemical composition of the pyrolysis product of bagasse with Ni/SBA catalysis (10% w/w). Based on the percent area value of the pyrolysis product identified on the pyrogram, the chemical composition of the pyrolysis product of bagasse produced was a cellulose/hemicellulose derivative product of 45.46%-60.24% and a lignin derivative product of 32.81%-17.77% . The addition of the catalyst Ni/SBA-15 to the pyrolysis of bagasse increased the amount of cellulose/hemicellulose derivative products such as ketones and furfural and then increased the amount of lignin derivative products such as vanillin and phenol. Keywords: Pyrolysis, Baggase, Catalyst Ni/SBA-15, Py-GC/MS